2003
DOI: 10.1161/01.cir.0000069270.16498.75
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of the CXCR3 Chemokine ITAC Are Associated With the Development of Transplant Coronary Artery Disease

Abstract: Background-Human

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 19 publications
4
37
0
Order By: Relevance
“…69 The relevant ECs may be those that line the arterial lumen or those that line microvessels of the adventitia. A pathway of selective recruitment, judged by selective CXCR3-binding chemokine expression, does appear to operate in human GA, [23][24][25][26][27] as well as in our human artery GA model. 38 These studies have demonstrated that CXCR3 and CCR5 ligands are synthesized in both the parenchymal and vascular compartments of human cardiac allografts.…”
Section: T H 1 Effector Cells and Cd8mentioning
confidence: 85%
See 1 more Smart Citation
“…69 The relevant ECs may be those that line the arterial lumen or those that line microvessels of the adventitia. A pathway of selective recruitment, judged by selective CXCR3-binding chemokine expression, does appear to operate in human GA, [23][24][25][26][27] as well as in our human artery GA model. 38 These studies have demonstrated that CXCR3 and CCR5 ligands are synthesized in both the parenchymal and vascular compartments of human cardiac allografts.…”
Section: T H 1 Effector Cells and Cd8mentioning
confidence: 85%
“…Notably, an increased expression of the IFN-␥-inducible chemokines RANTES (CCL5) and I-TAC and an increased expression of the T H 1-associated chemokine receptor CXCR3 have been described in arteriosclerotic coronary arteries. 25,26 The most convincing evidence for an association of IFN-␥ with GA was a recent detailed inventory of infiltrating leukocytes and cytokines in arteriosclerotic coronary arteries. van Loosdregt et al found that the expression of IFN-␥, IFN-␥-inducible chemokines (Mig, IP-10, ITAC, RANTES, and fractalkine/CX3CL1), and markers of IFN-␥-secreting T H 1 cells (CXCR3, CCR5, and CX3CR1) were increased in epicardial coronary arteries from transplanted hearts with documented GA compared with referent specimens.…”
Section: Evidence For a Pathogenetic Role Of Ifn-␥ In Gamentioning
confidence: 99%
“…It was demonstrated that patients with mild to moderate hypertension without coronary artery disease (CAD) have elevated serum levels of inflammatorymediators such as the C-C chemokines CCL2. As far as C-X-C chemokines are concerned, there is only one previous experience demonstrating a correlation between serum IFN-inducible T-cell a chemoattractant (I-TAC or CXCLll) levels and development of transplant CAD in humans (12).…”
mentioning
confidence: 99%
“…10,11 These chemokines and others such as RANTES (regulated on activation normal T cell expressed and secreted) and fractalkine are directly linked with CAV development in animal studies. [12][13][14] Studies for the role of chemokines in human CAV development are limited to 2 immunohistochemical investigations 15,16 and studies on human coronary arteries transplanted in severe combined immunodeficiency mice reconstituted with human peripheral blood mononuclear cells (PBMCs). 17,18 CAV develops in rodents as early as 14 days after transplantation, 12 but its course in humans is relatively slow.…”
mentioning
confidence: 99%